Adaptive Gain Controller Using Model Reference Adaptive Control Method Stability Approach For Road Vehicle Following System - M. R., Sapiee; Noordin, A. (Fakulti Kejuruteraan Mekanikal (FKM), Universiti Teknikal Malaysia Melaka (UTeM), 2010)
In order to maintain stability and satisfy operating constraints, the control system on the following vehicle needs information about the motion of preceding vehicle. A one-vehicle look-ahead control strategy is proposed and will be investigated for this operation. A mathematical model for this control strategy is obtained and simulated. This paper describes the process of designing an adaptive gain controller for a road vehicle following system. This is done through simulations and is further discussed to find the effectiveness of the method.